Atrial-ventricular function in rheumatic mitral regurgitation using strain imaging. Issue 2 (June 2020) - Meel, Ruchika; Peters, Ferande; Khandheria, Bijoy K; Libhaber, Elena; Essop, Mohammed
Abstract : Background: Chronic mitral regurgitation (MR) historically has been shown to primarily affect left ventricular (LV) function. The impact of increased left atrial (LA) volume in MR on morbidity and mortality has been highlighted recently, yet the LA does not feature as prominently in the current guidelines as the LV. Thus, we aimed to study LA and LV function in chronic rheumatic MR using traditional volumetric parameters and strain imaging. Methods: Seventy-seven patients with isolated moderate or severe chronic rheumatic MR and 40 controls underwent echocardiographic examination. LV and LA function were assessed with conventional echocardiography and 2D strain imaging. Results: LA stiffness index was greater in chronic rheumatic MR than controls (0.95 ± 1.89 vs 0.16 ± 0.13, P  = 0.009). LA dysfunction was noted in the reservoir, conduit, and contractile phases compared with controls ( P  < 0.05). LA peak reservoir strain (ƐR ), LA peak contractile strain, and LV peak systolic strain were decreased in chronic rheumatic MR compared with controls ( P  < 0.05). Eighty-six percent of patients had decreased LA ƐR and 58% had depressed LV peak systolic strain. Decreased ƐR and normal LV peak systolic strain were noted in 42%. Thirteen percent had normal ƐR and LV peak systolic strain. One patient had normal ƐR with decreased LV peak systolic strain. Conclusions: In chronic rheumatic MR, there is LA dysfunction in the reservoir, conduit, and contractile phases. In this study, LA dysfunction with or without LV dysfunction was the predominant finding, and thus, LA dysfunction may be an earlier marker of decompensation in chronic rheumatic MR.